Evaluasi Rehabilitasi Riparian Sungai Ranggeh dengan Indikator Komunitas - Jojok Sudarso; Imroatushshoolikhah; Aiman Ibrahim; Siti Aisyah; Laela Sari, (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Evaluation of Riparian Rehabilitation in River River Usingthe Macrozoobenthos Community Indicator. Macrozoobenthos organism is one of aquatic biota which is often used to assess the ecosystems health of river.The evaluation of riparian habitat rehabilitation using benthic macroinvertebrates has been commonly used in many countries. The purposes of this study were to evaluate the impact of Ranggeh river riparian rehabilitation and to determine environmental parameters that influenced benthic macroinvertebrate communities in Ranggeh River. This research was conductedfrom February to September 2019. Benthic macroinvertebrate Benthic macroinvertebrates, river, evaluation, EPT, rehabilitationsamples were collected using Hess Sampler in a sampling area of 0.2 m2. This evaluation was carried out after two months since the rehabilitation of riparian habitat completed. The results show that rehabilitation of the riparian habitat has changed the community, in the aspects of biological metrics of taxa number, abundance, and taxa numbersof Ephemeroptera, Plecoptera, and Trichoptera (EPT). Furthermore, the taxa number and EPT metrics increased after habitat rehabilitation, however the abundance decreased slightly. In addition, the taxa number metric was positively correlated with conductivity parameter (r = 0.8), but negatively correlatedto turbidity (r = -0.91) and pH (r = -0.77). Meanwhile, the EPT metric was negatively correlated with turbidity parameters (r = -0.76) and %embeddedness (r = -0.94). The total abundance metric was not sensitive to the parameters measured in this study. Meanwhile, biological metrics for taxa number and EPT can be used to assess rehabilitation success of river ecosystem habitats